Pericardial Grafting of Cardiac Progenitor Cells in Self-Assembling Peptide Scaffold Improves Cardiac Function After Myocardial Infarction - Masato Kanda; Toshio Nagai; Naomichi Kondo; Katsuhisa Matsuura; Hiroshi Akazawa; Issei Komuro; Yoshio Kobayashi (Cell Transplantation, 2023)
Many studies have explored cardiac progenitor cell (CPC) therapy for heart disease. However, optimal scaffolds are needed to ensure the engraftment of transplanted cells. We produced a three-dimensional hydrogel scaffold (CPC-PRGmx) in which high-viability CPCs were cultured for up to 8 weeks. CPC-PRGmx contained an RGD peptide-conjugated self-assembling peptide with insulin-like growth factor-1 (IGF-1). Immediately after creating myocardial infarction (MI), we transplanted CPC-PRGmx into the pericardial space on to the surface of the MI area. Four weeks after transplantation, red fluorescent protein-expressing CPCs and in situ hybridization analysis in sex-mismatched transplantations revealed the engraftment of CPCs in the transplanted scaffold (which was cellularized with host cells). The average scar area of the CPC-PRGmx-treated group was significantly smaller than that of the non-treated group (CPC-PRGmx-treated group = 46 ± 5.1%, non-treated MI group = 59 ± 4.5%; p < 0.05). Echocardiography showed that the transplantation of CPC-PRGmx improved cardiac function and attenuated cardiac remodeling after MI. The transplantation of CPCs-PRGmx promoted angiogenesis and inhibited apoptosis, compared to the untreated MI group. CPCs-PRGmx secreted more vascular endothelial growth factor than CPCs cultured on two-dimensional dishes. Genetic fate mapping revealed that CPC-PRGmx-treated mice had more regenerated cardiomyocytes than non-treated mice in the MI area (CPC-PRGmx-treated group = 0.98 ± 0.25%, non-treated MI group = 0.25 ± 0.04%; p < 0.05). Our findings reveal the therapeutic potential of epicardial-transplanted CPC-PRGmx. Its beneficial effects may be mediated by sustainable cell viability, paracrine function, and the enhancement of de novo cardiomyogenesis.